Effect of Black Soldier Fly and Bromelain Extracts supplementation on digestibility, growth performance in Giant Freshwater Prawn under a complete Recirculating Aquaculture System water system - Karnchanamayoon, Karnchana; Tongsiri, Sudaporn; Pimpimol, Tipsukhon; Whangchai, Niwooti; Klahan, Rungkan (International Journal of Aquatic Research and Environmental Studies, 2026)
Currently, farmers cultivating giant freshwater prawns (Macrobrachium rosenbergii)  encounter challenges like low survival rates, slow growth, and high production costs. This research aims 1) to study the optimized conditions of bromelain to digest black soldier fly larvae  - BFSL (H. illucens), which is included as a protein source in giant freshwater prawn feeds, 2) to study the suitable level of bromelain enzymes for growth enhancement of giant freshwater prawn, and 3) to study the pattern of using BFSL and bromelain for giant freshwater prawn production. The first experiment studied the digestibility of 2 enzymes: bromelain extracted from pineapples and protease extracted from the hepatopancreas. Results showed that bromelain digestion activities in BSFL were higher than those of protease at every pH at both 25°C and 30°C temperatures. In the second experiment, growth performance, feed efficiency, and cost-effectiveness were evaluated in four different treatments for 90 days. T1- control feeds without BFSL and bromelain, T2- control feeds supplemented with 250 ppt bromelain, T3- Feeds included 12% BFSL, and T4 - Feeds included 12% BFSL supplemented with 250 ppt bromelain. The growth performance in T3 and T4 outperformed other treatments. No disparities were detected in feeding efficiency and feed conversion ratio. Giant freshwater prawns fed with BSFL supplementation exhibited the highest observed values in the molecular structure of chitin content within their shells. The chitin structure, analyzed using FTIR and X-ray diffusion techniques, displayed features indicative of α-chitin, evidenced by a peak in the spectrum between 2,000 - 1,500 cm-1. Consequently, this study suggests that supplementing BSFL and bromelain holds promise for reducing costs in aquaculture.
Keywords: Black soldier fly; Bromelain; Digestibility; Giant freshwater prawn (Macrobrachium rosenbergii); Growth performance